A simple and robust approach for 2D-simulation of reinforced concrete member. (August 2021) - Arslan, Abdussamet; Gümüş, Muhammed
Abstract: Over the past years, features of the computers aided numerical simulations of reinforced concrete (RC) have been improved with increasing technological developments. However, some difficulties remain such as modelling of snap-back behavior of quasi-brittle materials and convergence issue resulted from shape of the constitutive material law. In this study, a novel approach for the 2D nonlinear numerical modelling of the reinforced concrete member is presented. The proposed method of Linear Degradation Analysis (LDA) is developed integrating the isotropic continuum damage mechanic and the solution algorithm of lattice model. The main distinctive property of LDA is to combine simplicity of homogeneously distributed crack assumption and robustness of using secant stiffness reduction. In order to demonstrate the validity of LDA, several RC member containing beam, slab and frame from the literature are simulated. It can be concluded from the verification that the accuracy of the linear degradation analysis method is approved by remarkable similarity between the simulation and the experiment with regard to damage pattern and load displacement behavior.